AR Moon Stellar Explorer: An Immersive Learning Tool for Year 5 Students - Chandran, Yugeswary; Rahayu A Hamid (Applied Information Technology And Computer Science, 2025)
The integration of Augmented Reality (AR) in educational applications has garnered attention for its potential to engage students more effectively in Science learning. The AR Moon & Stellar Explorer application enhances Year 5 students’ understanding of astronomy by providing interactive and immersive experiences centered on the phases of the moon and constellations. This project is particularly significant in addressing the challenges faced by Malaysian students transitioning from learning Science in their native languages to English-based curricula. By offering an AR-based English-learning environment, the application not only bridges this language gap but also fosters a deeper comprehension of complex astronomical phenomena. Developed using the Multimedia Mobile Content Development (MMCD) methodology, the application features interactive elements such as 3D models, AR sessions, and gamified quizzes, creating an engaging and dynamic learning environment that accommodates various learning styles and ensures students grasp both the scientific content and relevant English terminology. Targeting Year 5 students, beta testing revealed a positive satisfaction rate of 84.6%, confirming that the AR Moon & Stellar Explorer application effectively enhances learning outcomes and is well-received by users, despite some challenges with professional terminology.